Tephra dispersal and eruption dynamics of wet and dry phases of the 1875 eruption of Askja Volcano, Iceland - Rebecca Carey; Houghton, BF; Thordarson, T (2010)
The 1875 rhyolitic eruption of Askja volcano in Iceland was a complex but well-documented silicic explosive eruption. Eyewitness chronologies, coupled with examination of very proximal exposures and historical records of distal deposit thickness, provide an unusual opportunity for study of Plinian and phreatoplinian eruption and plume dynamics. The ~17 hour-long main eruption was characterized by abrupt and reversible shifts in eruption style, e. g., from 'wet' to 'dry' eruption conditions, and transitions from fall to flow activity. The main eruption began with a 'dry' subplinian phase (B), followed by a shift to a very powerful phreatoplinian 'wet' eruptive phase (C1). A shift from sustained 'wet' activity to the formation of 'wet' pyroclastic density currents followed with the C2 pyroclastic density currents, which became dryer with time. Severe ground shaking accompanied a migration in vent position and the onset of the intense 'dry' Plinian phase (D). Each of the fall units can be modeled using the segmented exponential thinning method (Bonadonna et al. 1998), and three to five segments have been recognized on a semilog plot of thickness vs. area1/2. The availability of very proximal and far-distal thickness data in addition to detailed observations taken during this eruption has enabled calculations of eruption parameters such as volumes, intensities and eruption column heights. This comprehensive dataset has been used here to assess the bias of volume calculations when proximal and distal data are missing, and to evaluate power-law and segmented exponential thinning methods using limited datasets. Â© Springer-Verlag 2009.